Correlation Analysis of High School Major, Academic Achievement, Major Choice in SPAN, University Study Program, and Cumulative Grade Point Average of Achieving Students via the SPAN Pathway at UIN Mataram - Masnun Masnun; Adi Fadli; Endrawati Endrawati (ISLAMIKA, 2026)
This study aims to analyze the relationship between high school major, academic and non-academic achievement, major choice through the National Academic Achievement Selection (SPAN) PTKIN pathway, the major pursued at the university, and the Cumulative Grade Point Average (GPA) of achieving students via the SPAN pathway at UIN Mataram. This research uses a quantitative approach with a correlational research type. The research location is UIN Mataram, with a sample size of 1,768 students admitted through the SPAN pathway. Data collection techniques were carried out through surveys and documentation of student academic data, including data on high school major, academic/non-academic achievement, SPAN major choice, university major, and GPA. Research instruments included questionnaires and academic data documentation sheets sourced from official institutional archives. Data analysis techniques used Pearson Product Moment correlation tests to determine the relationship between research variables. The results show a positive and significant correlation between major choice in SPAN and the major pursued at UIN Mataram, as well as a negative and significant correlation between university major and student GPA. Additionally, a negative and significant correlation was found between major choice in SPAN and academic/non-academic achievement in high school. Meanwhile, no significant relationship was found between high school major and university major, high school achievement, or GPA, and no significant relationship was found between academic/non-academic achievement and GPA. The implications of this research indicate that students’ academic success in higher education is not solely determined by their major and achievement at the secondary education level but is more influenced by the suitability of major choice, characteristics of the study program, and the learning context in higher education. These findings can serve as a basis for developing more comprehensive, interest- and potential-based student selection policies and career guidance services.